Thickness evolution of transport properties in exfoliated Fe1+yTe nanoflakes. (26th June 2018) - Hsieh, T-W; Zou, T; Hu, J; Mao, Z Q; Zhang, P P; Ke, X
Abstract: We report the evolution of transport properties in exfoliated Fe1+ y Te ( y   =  0.04) nanoflakes of various thickness. In contrast to the sharp semiconducting-to-metallic phase transition observed in both bulk and thicker flakes, this transition becomes broadened for flakes with an intermediate thickness followed by the appearance of a superconducting-like feature upon further cooling. With the thickness further decreased, the flakes exhibit insulating transport behavior with significantly enhanced positive magnetoresistance, which can be explained using a variable range hopping mechanism, suggesting the nature of a highly disordered 2D system.